Gothic music : the sounds of the uncanny - Elferen, Isabella van (Gothic literary studies., 2012)
Gothic Music: The Sounds of the Uncanny traces sonic Gothic through history and genres from the eighteenth-century ghost story through the spooky soundtracks of cinema, television and video games to the dark music of the Goth subculture.